2013
DOI: 10.1115/1.4023700
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Empirical Damage Model for Aging and in Vivo Injury of the Murine Patellar Tendon

Abstract: While useful models have been proposed to predict the mechanical impact of damage in tendon and other soft tissues, the applicability of these models for describing in vivo injury and age-related degeneration has not been investigated. Therefore, the objective of this study was to develop and validate a simple damage model to predict mechanical alterations in mouse patellar tendons after aging, injury, or healing. To characterize baseline properties, uninjured controls at age 150 days were cyclically loaded ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Future studies will investigate regional changes to the injury site that may further enhance the ability of measured structural properties to predict mechanical properties that may be reduced by averaging throughout the entire tissue. Work is being completed to develop a healing model (Buckley MR, 2013; Duenwald-Kuehl et al, 2012) that can predict mechanical properties throughout healing from structural properties.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will investigate regional changes to the injury site that may further enhance the ability of measured structural properties to predict mechanical properties that may be reduced by averaging throughout the entire tissue. Work is being completed to develop a healing model (Buckley MR, 2013; Duenwald-Kuehl et al, 2012) that can predict mechanical properties throughout healing from structural properties.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 This may suggest novel differences in the biology of damage resulting from either aging processes or the repair response to injury. 7 For example, it is possible that higher strains pose a greater risk to healing tendons while prolonged repetitive stress poses a greater risk to the aging tendon.…”
Section: Discussionmentioning
confidence: 99%
“…Pilot studies demonstrated that murine patellar tendon mechanical properties decline significantly between 120 and 270 days post-natal (data not shown). Therefore, 120-day old mice were considered “mature” while 270-day old mice were considered “aged.” At 270 days post-natal, 30-35 aged animals of each genotype (WT: n=30, Bgn −/− :n=31, Dcn −/− :n=35) underwent bilateral surgery on their patellar tendons as previously described (Beason et al, 2012; Buckley et al, 2013; Dunkman et al, 2013b; Lin et al, 2006). Briefly, after cutting the skin, incisions were made along the side of the tendon to allow for a rubber coating backing to slip under the tendon.…”
Section: Methodsmentioning
confidence: 99%
“…Throughout preparation, the tendon was kept hydrated with PBS. The dynamic testing protocol consisted of 1) preconditioning, 2) stress relaxation at strain levels of 4%, 6% and 8%, 3) a sinusoidal frequency sweep (10 cycles at 0.01, 0.1, 1, 5, and 10 Hz) at each strain level, 4) return to gauge length, and 5) ramp to failure(Buckley et al, 2013; Dourte et al, 2012; Dourte et al, 2013; Dunkman et al, 2013a, b; Lujan et al, 2009). …”
Section: Methodsmentioning
confidence: 99%